Correction: Macroevolution of gastric Helicobacter species unveils interspecies admixture and time of divergence (The ISME Journal, (2018), 12, 10, (2518-2531), 10.1038/s41396-018-0199-5) - Smet, Annemieke; Yahara, Koji; Rossi, Mirko; Tay, Alfred; Backert, Steffen; Enßer, Armin; Fox, James G.; Flahou, Bram; Ducatelle, Richard; Haesebrouck, Freddy; Corander, Jukka (Isme Journal, 2019)
The original version of this Article contained an error in the presentation of the author Armin Ensser, which was incorrectly given as Ensser Armin. The correct author list is as follows: Annemieke Smet, Koji Yahara, Mirko Rossi, Alfred Tay, Steffen Backert, Armin Ensser, James G. Fox, Bram Flahou, Richard Ducatelle, Freddy Haesebrouck, Jukka Corander The authors apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2019-05-28